Unravelling Soil Fungal Communities from Different Mediterranean Land-Use Backgrounds - Orgiazzi, Alberto; Lumini, Erica; Nilsson, R Henrik; Girlanda, Mariangela; Vizzini, Alfredo; Bonfante, Paola; Bianciotto, Valeria (PLoS ONE, 2012)
Background Fungi strongly influence ecosystem structure and functioning, playing a key role in many ecological services as decomposers, plant mutualists and pathogens. The Mediterranean area is a biodiversity hotspot that is increasingly threatened by intense land use. Therefore, to achieve a balance between conservation and human development, a better understanding of the impact of land use on the underlying fungal communities is needed. Methodology/Principal Findings We used parallel pyrosequencing of the nuclear ribosomal ITS regions to characterize the fungal communities in five soils subjected to different anthropogenic impact in a typical Mediterranean landscape: a natural cork-oak forest, a pasture, a managed meadow, and two vineyards. Marked differences in the distribution of taxon assemblages among the different sites and communities were found. Data analyses consistently indicated a sharp distinction of the fungal community of the cork oak forest soil from those described in the other soils. Each soil showed features of the fungal assemblages retrieved which can be easily related to the above-ground settings: ectomycorrhizal phylotypes were numerous in natural sites covered by trees, but were nearly completely missing from the anthropogenic and grass-covered sites; similarly, coprophilous fungi were common in grazed sites. Conclusions/Significance Data suggest that investigation on the below-ground fungal community may provide useful elements on the above-ground features such as vegetation coverage and agronomic procedures, allowing to assess the cost of anthropogenic land use to hidden diversity in soil. Datasets provided in this study may contribute to future searches for fungal bio-indicators as biodiversity markers of a specific site or a land-use degree.
Keywords: air pollution; ecosystem services; ecosystems; Forests; Grazing Lands (citation); Italy; land use; Micro Organisms; Soil Capability

Modelling the influence of peri-urban trees in the air quality of Madrid region (Spain). - Alonso, Rocío; Vivanco, Marta G; González-Fernández, Ignacio; Bermejo, Victoria; Palomino, Inmaculada; Garrido, Juan Luis; Elvira, Susana; Salvador, Pedro; Artíñano, Begoña (Environmental pollution (Barking, Essex : 1987), 2011)
Tropospheric ozone (O(3)) is considered one of the most important air pollutants affecting human health. The role of peri-urban vegetation in modifying O(3) concentrations has been analyzed in the Madrid region (Spain) using the V200603par-rc1 version of the CHIMERE air quality model. The 3.7 version of the MM5 meteorological model was used to provide meteorological input data to the CHIMERE. The emissions were derived from the EMEP database for 2003. Land use data and the stomatal conductance model included in CHIMERE were modified according to the latest information available for the study area. Two cases were considered for the period April-September 2003: (1) actual land use and (2) a fictitious scenario where El Pardo peri-urban forest was converted to bare-soil. The results show that El Pardo forest constitutes a sink of O(3) since removing this green area increased O(3) levels over the modified area and over down-wind surrounding areas.
Keywords: Air Pollutants; Air Pollutants: analysis; Air Pollutants: metabolism; air pollution; Air pollution removal; Air Pollution: statistics & numerical data; Air quality models; Chemical; Cities; Dry deposition; Environmental Monitoring; Environmental Monitoring: methods; Models; Ozone; Ozone: analysis; Ozone: metabolism; Spain; Trees; Trees: classification; Trees: metabolism; Trees: physiology; Urban forest

Morphological and physiological response of two populations of Quercus ilex L. to SO2 fumigation - Infante, J M; Garcia-Laureano, R; Merino, J (PHYTON-ANNALES REI BOTANICAE, 2002)
Quercus ilex L., is the predominant evergreen schlerophyllous tree in the Mediterranean landscape of the Iberian Peninsula. Fruit acorns were collected in two populations located in the center (southern Spain) and at the northern border (northern Spain; a distance of 800 km) of the distribution area of Quercus ilex. One-month-old potted plants were grown for 130 days to a high SO2 concentration (0.23 ppm, 14 h d(-1)) under controlled climate conditions. Both northern and southern plants underwent a significant decrease in growth rate as a consequence of the treatment. Even so, plants appear to be quite resistant to SO2 compared with either more temperate or more productive species. The southern population was more sensitive to the treatment, as reflected by the bigger decrease in both growth and photosynthetic rates. Differences in resistance appear to be related to the biogeographic origin of the populations studied, which underlines the importance of biogeographic aspects in studies of resistance to air pollutants.
Keywords: air pollution; Mediterranean ecosystems; Populations; Quercus ilex; Sulfur Dioxide

Effects of environmental stress on forest crown condition in Europe. Part II: Estimation of stress induced by meteorology and air pollutants - Leeuwen, E. P. Van; Hendriks, KCMA (Water, Air, & Soil Pollution, 2000)
In order to assess the relationship between environmental stress and crown condition of forest trees monitored since 1986 in Europe, estimates of stress factors, including temperature stress, drought stress and air pollution stress, were derived with the best data, methods and models currently available. This paper presents information on the methods used to derive such stress factors, and on the overall ranges, the temporal trends, the spatial distribution and the reliability of the calculated stress factors. The temperature stress indices did not show much temporal variation between 1985 to 1995. As expected spatial patterns were north-south orientated, going from colder northern regions to warmer southern regions. The calculated relative transpiration showed a more complex pattern, coinciding to a large extend with patterns of rainfall and temperature. Potential acid deposition decreased between 1986 and 1992, but remained fairly constant after 1992. The strong decrease was mainly the result of the decrease in SOx deposition, and to a small decrease in NOy deposition. Highest levels of the S and N deposition were calculated in Central and Western Europe. Base cation deposition was largest in coastal areas and in southern Europe. This is mainly due to soil dust, Sahara dust and sea salt. Base cation deposition can compensate almost entirely for the potential inputs in the south of Europe, whereas in central Europe it equalled about 25% of the potential acid input. A comparison between site speciﬁc modelled deposition and deposition derived from throughfall data showed that the total acid deposition is usually overestimated by the model, whereas the total nitrogen deposition is underestimated, especially at plots with high nitrogen loads. There is, however, a signiﬁcant correlation between measured and modelled data for all S and N deposition, thus allowing their use in a statistical analyses.
Keywords: acidity; air pollution; ammonia; atmospheric deposition; Base cations; deposition model; Drought; nitrogen oxides; Ozone; sulphur; temperature stress; water balance

Effects of environmental stress on forest crown condition in Europe. Part IV: statistical analysis of relationships - Klap, J M; Voshaar, J H Oude (Water, Air, & Soil …, 2000)
Site-speciﬁc estimates for various environmental stress factors were related with measured crown condition data at a systematic 16 16 km2 grid over Europe, according to previously stated hypotheses, using a multiple regression approach, including interactions, and lagged effects of stress factors. Methodological differences among countries accounted for >30% of the variation in defoliation. Nevertheless, crown condition was found to vary naturally with tree age, altitude, drought stress and, most likely, also pathogenic fungi and insects. Signiﬁcant impacts of air pollution (speciﬁcally ozone but also NOx , SOx and acid deposition) were found at regional levels in parts of central Europe, particularly for deciduous species. Impacts seemed less signiﬁcant for conifers, especially for spruce, but this might be affected by confounding effects or strong correlations between (a harsh) climate and (low) atmospheric deposition in the area where spruce predominates. National studies indicate that ozone and acid deposition can have a signiﬁcant effect on the defoliation of spruce as well. We conclude that while forest condition varies naturally, continued emissions will contribute further to forest decline in the long term.
Keywords: acid deposition; air pollution; correlative study; critical load; defoliation; Fagus sylvatica; forest vitality; meteorological stress; picea abies; Pinus sylvestris; Quercus ilex; Quercus petraea; Quercus robur

Response of two populations of holm oak (Quercus rotundifolia Lam.) to sulfur dioxide. - García, D; Rodríguez, J; Sanz, J M; Merino, J (Ecotoxicology and environmental safety, 1998)
Experiments were carried out with seedlings of Quercus rotundifolia Lam., an evergreen schlerophyllous tree typical of the Spanish Mediterranean climate environments. Fruits were collected in two distant (800 km) populations located in the center (southern Spain) and northern border (northern Spain) of the area of distribution of the species. One-month-old potted plants were grown for 130 days in an enriched atmosphere of SO2 (0.23 ppm, 14 h/day) in controlled (growth chamber) conditions. Both northern and southern plants underwent a significant decrease in growth rate as a consequence of the treatment. Even so, plants appear to be quite resistant to SO2 compared with either more temperate or more productive species. The southern population was more sensitive to the treatment, as reflected by the bigger decrease in both growth and photosynthetic rates. Differences in resistance appear to be related to the biogeographic origin of the populations studied, which underlines the importance of biogeographic aspects in studies of resistance to air pollutants.
Keywords: Adaptation; Air Pollutants; Air Pollutants: adverse effects; air pollution; biomass; Environment; GROWTH RATE; photosynthesis; Photosynthesis: physiology; Physiological; Plant physiology; Pollutants; Quercus rotundifolia; Sulfur Dioxide; Sulfur Dioxide: adverse effects; Sulphur dioxide; Trees; Trees: drug effects; Trees: genetics; Trees: physiology

Response of two populations of holm oak (Quercus rotundifolia Lam.) to sulfur dioxide. - García, D.; Rodríguez, J.; Sanz, J. M.; Merino, J. (Ecotoxicology and environmental safety, 1998)
Experiments were carried out with seedlings of Quercus rotundifolia Lam., an evergreen schlerophyllous tree typical of the Spanish Mediterranean climate environments. Fruits were collected in two distant (800 km) populations located in the center (southern Spain) and northern border (northern Spain) of the area of distribution of the species. One-month-old potted plants were grown for 130 days in an enriched atmosphere of SO2 (0.23 ppm, 14 h/day) in controlled (growth chamber) conditions. Both northern and southern plants underwent a significant decrease in growth rate as a consequence of the treatment. Even so, plants appear to be quite resistant to SO2 compared with either more temperate or more productive species. The southern population was more sensitive to the treatment, as reflected by the bigger decrease in both growth and photosynthetic rates. Differences in resistance appear to be related to the biogeographic origin of the populations studied, which underlines the importance of biogeographic aspects in studies of resistance to air pollutants.
The following values have no corresponding Zotero field: accession-num: 9626534
Keywords: Adaptation; Air Pollutants; Air Pollutants: adverse effects; air pollution; biomass; Environment; GROWTH RATE; photosynthesis; Photosynthesis: physiology; Physiological; Plant physiology; Pollutants; Quercus rotundifolia; Sulfur Dioxide; Sulfur Dioxide: adverse effects; Sulphur dioxide; Trees; Trees: drug effects; Trees: genetics; Trees: physiology

Tree bark as a bioindicator of air pollution in Navarra, Spain - Santamaria, J M; Martin, A (Water, Air, & Soil Pollution, 1997)
During a two year research period from 1992 to 1993, samples of different species of trees were taken in 17 forest stands located in Navarra, Spain. From these samples, bark extracts were prepared in which the pH and the conductivity were measured. The health of the sampling trees was also evaluated by determining the degree of defoliation and decoloration of the canopies. The bark tissue analysis revealed the presence of an environmental acidity gradient that decreased from NW to SE. This coincides with the location of important sources of pollution and their course of transport and dispersion. On the other hand, in the samples of Quercus ilex a significant correlation between the pH and the defoliation levels (P<0.01, r = 0.62) was found. This fact reveals the potential usefulness of tree bark as a health bioindicator of trees.
Keywords: air pollution; Bioindicator; biomonitoring; Tree bark

Leaf Contamination by Atmospheric Pollutants as Assessed by Elemental Analysis of Leaf Tissue, Leaf Surface Deposit and Soil - Alfani, Anna; Maisto, Giulia; Iovieno, Paola; Rutigliano, Flora a.; Bartoli, Giovanni (Journal of Plant Physiology, 1996)
In order to evaluate the influence of air pollutants influx on leaf elemental composition, the concentration ofN, S, Cu, Fe and Pb were analyzed in the surface deposit and tissue of Quercus ilex L. leaves from 8 sites of the urban area of Naples. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total contents of Nand S and for available contents ofCu, Fe and Pb. In the leafsurface deposit S content was high though significantly (P<O.OOl) lower than in the leaf tissue, whilst N was not detectable. Cu, Pb and Fe contents in leafsurface deposit were conspicuous. The Pb content was higher in the leafsurface deposit than in the leaf tissue. No correlation between leaftissue and surface deposit contents was found for S or for Fe. By contrast, positive and significant correlations (P < 0.01) were found between leaf deposit and leaf tissue for both Cu and Pb. Nand S contents in the leaves were not correlated to the respective contents in the soil and the same was also found for Cu and Fe. In contrast with the presence of limiting concentrations in the soil, N, S and Fe leaf contents were significantly higher than in the leaves from remote sites. The data suggest that direct uptake of airborne pollutants, in addition to root absorption, may influence leaf elemental composition of Q. ilex L. leaves.
Keywords: air pollution; leaf contamination; nitrogen; Quercus ilex L; sulphur; Trace metals

Leaf Contamination by Atmospheric Pollutants as Assessed by Elemental Analysis of Leaf Tissue, Leaf Surface Deposit and Soil - Alfani, Anna; Maisto, Giulia; Iovieno, Paola; Rutigliano, Flora a; Bartoli, Giovanni (Journal of Plant Physiology, 1996)
In order to evaluate the influence of air pollutants influx on leaf elemental composition, the concentration ofN, S, Cu, Fe and Pb were analyzed in the surface deposit and tissue of Quercus ilex L. leaves from 8 sites of the urban area of Naples. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total contents of Nand S and for available contents ofCu, Fe and Pb. In the leafsurface deposit S content was high though significantly (P<O.OOl) lower than in the leaf tissue, whilst N was not detectable. Cu, Pb and Fe contents in leafsurface deposit were conspicuous. The Pb content was higher in the leafsurface deposit than in the leaf tissue. No correlation between leaftissue and surface deposit contents was found for S or for Fe. By contrast, positive and significant correlations (P < 0.01) were found between leaf deposit and leaf tissue for both Cu and Pb. Nand S contents in the leaves were not correlated to the respective contents in the soil and the same was also found for Cu and Fe. In contrast with the presence of limiting concentrations in the soil, N, S and Fe leaf contents were significantly higher than in the leaves from remote sites. The data suggest that direct uptake of airborne pollutants, in addition to root absorption, may influence leaf elemental composition of Q. ilex L. leaves.
The following values have no corresponding Zotero field: publisher: Gustav Fischer Verlag, Stuttgart
Keywords: air pollution; leaf contamination; nitrogen; Quercus ilex L; sulphur; Trace metals